2023
DOI: 10.1111/bjso.12696
|View full text |Cite
|
Sign up to set email alerts
|

Ableism differs by disability, gender and social context: Evidence from vignette experiments

Shane Timmons,
Frances McGinnity,
Eamonn Carroll

Abstract: Existing research on prejudice and discrimination towards disabled people (i.e. ‘ableism’) has conceptualized it as a general attitude, obscuring the role of social context in its manifestation. We aimed to investigate whether and how ableism manifests differently depending on the nature of the disability, the disabled person's gender and the social context of the interaction. A nationally representative sample of 2000 adults read a series of vignettes about issues faced by disabled people (e.g. employment, re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Similar to the policy questions presented in the previous section, this vignette experiment was fielded as part of a larger study of attitudes to disability in Ireland in August 2022 (Timmons et al, 2023a). While the overall survey contained 2,000 participants, the vignettes experiment was designed so that each version of the vignette would be shown to at least 250 participants (see Timmons et al, 2023b).…”
Section: Notementioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the policy questions presented in the previous section, this vignette experiment was fielded as part of a larger study of attitudes to disability in Ireland in August 2022 (Timmons et al, 2023a). While the overall survey contained 2,000 participants, the vignettes experiment was designed so that each version of the vignette would be shown to at least 250 participants (see Timmons et al, 2023b).…”
Section: Notementioning
confidence: 99%
“…While the acceptability of objection against Ukrainian refugees was slightly higher than for asylum seekers (see Figure 5.4), this difference in judgement was not statistically significant (χ² = 0.64, p = .422). NDA Vignette experiments of attitudes to disability (Timmons et al, 2023b).…”
Section: Notementioning
confidence: 99%
“…Sixty per cent of these respondents reported worsening financial situations and over 70 per cent reported that COVID-19 affected their ability to pay 11 Defined as prejudice, discrimination, and the application of stigma toward people with disabilities (Friedman and Owen, 2017; see also Timmons et al, 2023).…”
Section: Disparities By Disability Statusmentioning
confidence: 99%